2014
DOI: 10.1111/1365-2745.12346
|View full text |Cite
|
Sign up to set email alerts
|

Does functional trait diversity predict above‐ground biomass and productivity of tropical forests? Testing three alternative hypotheses

Abstract: Summary1. Tropical forests are globally important, but it is not clear whether biodiversity enhances carbon storage and sequestration in them. We tested this relationship focusing on components of functional trait biodiversity as predictors. 2. Data are presented for three rain forests in Bolivia, Brazil and Costa Rica. Initial above-ground biomass and biomass increments of survivors, recruits and survivors + recruits (total) were estimated for trees ≥10 cm d.b.h. in 62 and 21 1.0-ha plots, respectively. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

56
290
12
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 331 publications
(366 citation statements)
references
References 70 publications
56
290
12
8
Order By: Relevance
“…These above results provide support for the general hypothesis that plant economics may not only be reflected in leaves, but also in stems at species (Freschet et al, 2010) and at community level (Perez-Ramos et al, 2012). However, most of the studies focusing on the relationship between FTD and C stocks did not consider the whole plant coordination and root traits are particularly ignored due to technical difficulties and are often substituted by measurement of leaf functional traits (Conti and Diaz, 2013;Cavanaugh et al, 2014;Finegan et al, 2015). It is recommended to include root traits, in addition to leaf and stem traits, in further studies concerning FTD and C stocks in natural forest ecosystems (Orwin et al, 2010;Grigulis et al, 2013).…”
Section: Role Of the Plant Economics Spectrum In Ftd-carbon Stocks Resupporting
confidence: 64%
See 4 more Smart Citations
“…These above results provide support for the general hypothesis that plant economics may not only be reflected in leaves, but also in stems at species (Freschet et al, 2010) and at community level (Perez-Ramos et al, 2012). However, most of the studies focusing on the relationship between FTD and C stocks did not consider the whole plant coordination and root traits are particularly ignored due to technical difficulties and are often substituted by measurement of leaf functional traits (Conti and Diaz, 2013;Cavanaugh et al, 2014;Finegan et al, 2015). It is recommended to include root traits, in addition to leaf and stem traits, in further studies concerning FTD and C stocks in natural forest ecosystems (Orwin et al, 2010;Grigulis et al, 2013).…”
Section: Role Of the Plant Economics Spectrum In Ftd-carbon Stocks Resupporting
confidence: 64%
“…However, Cavanaugh et al (2014) conducted a global scale study in natural tropical forests and found a positive relationship between CWM of maximum diameter and C stocks, suggests that characteristics of the dominant trees (specifically their maximum potential diameter) results greatest aboveground C stock in mature forests, strongly supported the mass ratio hypothesis. Cavanaugh et al (2014) and Finegan et al (2015) did not find a significant relationship between FD and C stock which is in disagreement with the niche complementarity hypothesis (Tilman et al, 1997). Although, Cavanaugh et al (2014) found a positive association between taxonomic diversity and C stocks, supports partly the niche complementarity hypothesis.…”
Section: Strong Evidences For the Mass Ratio Hypothesis And Poor Evidmentioning
confidence: 66%
See 3 more Smart Citations